A laboratory and in situ postexposure feeding assay with a freshwater snail - Correia, Vânia (2013)
Contaminant-driven feeding inhibition has direct and immediate consequences at higher levels of biological organization, by depressing the population consumption and thus hampering ecosystem functioning (e.g., grazing, organic matter decomposition). The present study aimed at developing a short-term laboratory and in situ assay based on the postexposure feeding of the freshwater snail Theodoxus fluviatilis. A method to precisely quantify feeding rates was first developed, consisting of a 3-h feeding period, in darkness, on 150 defrosted nauplii of the brine shrimp Artemia franciscana. Postexposure feeding after a 48-h exposure to cadmium was approximately as sensitive as survival, with the median effective concentration (EC50) and median lethal concentration (LC50) being 85 mg/L and 102 mg/L, respectively, and the 20% effective concentration (EC20) and 20% lethal concentration (LC20) being 41 mg/L and 77 mg/L, respectively. Together, both effects at the LC20 reduced population consumption by 56%. In situ experiments at reference sites covering broad ranges of current velocity, hardness, conductivity, sediment organic matter content, and sediment particle size distribution revealed the influence of these abiotic conditions on postexposure feeding, in the absence of contamination, to be negligible. The effectiveness of the in situ assay was evaluated at 5 sites contaminated with acid mine drainage. Surviving organisms at the single partially lethal site (37% mortality) presented a 54% feeding inhibition relative to the reference, whereas the population consumption would be inhibited by 71%, confirming the integration of survival and feeding to be pertinent for estimating contaminant effects at higher levels of biological organization.